Antimicrobial, Antioxidant and Cytotoxic Potential of Aerial Parts of Monotheca buxifolia - Sajjad Ahmad; Maimoona Gull; Asma Shah; Faiz Ullah Khan; Muhammad Rafiq; Ghusia Lutfullah; Alam Zeb Khan; Farhat Amin; Noreen Azhar; Muhammad Saleem Khan (Institute for Research and Community Services (LPPM) ITB, 2019)
In this study, different aerial parts of Monotheca Buxifolia were screened for their antibacterial, antifungal, and anti-oxidant activity. Extract of the fruit was most active against P. mirabilis, MSSA and M. morganii strains. Moreover, the methanolic fruit extract demonstrated good antibacterial properties against VRSA, S. aureus and Acinetobacter. Despite having good antibacterial properties, Monotheca buxifolia showed low antifungal activity. The cytotoxic activity was the highest in the pet-ether fruit extract, causing 60% of lethality against Artemia salina larvae with LD50 at 3.307. The highest scavenging activity was shown by the methanolic leaf extract in a concentration-dependent pattern. The findings of this study suggest that Monotheca Buxifolia has good antibacterial, antioxidant potential but low antifungal properties.